Pengaruh Penambahan Limbah Keramik terhadap Nilai CBR pada Campuran Tanah Lunak (Studi Kasus: Pembangunan Jalan Tol Trans Sumatera Ruas Betung (Simpang Sekayu) – Tempino – Jambi Seksi 2B) - Rival Tanjung; Totoh Andayono (Lembaga Yasin AlSys, 2026)
Although soft soil stabilization has been widely studied, research that specifically examines the use of ceramic waste as a subgrade soil stabilization material on the Proyek Pembangunan Jalan Tol Trans Sumatera Ruas Betung (Simpang Sekayu)–Tempino–Jambi Seksi 2B remains limited. This study aimed to analyze the effect of adding ceramic waste on improving the bearing capacity of soft soil based on California Bearing Ratio (CBR) values. A quantitative approach with a laboratory experimental design was employed, using soft soil samples taken at STA 110+600 in Musi Banyuasin Regency through purposive sampling. Ceramic waste was used as a stabilization material with dosage variations of 5%, 10%, 15%, and 20% of the soil weight. Data were collected through tests of physical soil properties, standard Proctor compaction, and CBR tests under unsoaked and soaked conditions, then analyzed quantitatively and supported by a One Sample t-test using SPSS software. The results showed that the addition of ceramic waste significantly increased the soil CBR values, with the highest value obtained for the 20% ceramic waste mixture. In addition, ceramic waste was found to reduce soil plasticity and increase the density achieved by compaction. These findings indicate that ceramic waste has the potential to be utilized as a relatively low-cost stabilization material for clayey soils to support more sustainable road construction and provide an empirical basis for the use of construction waste in improving subgrade performance in pavement structures.